Impurity-enhanced core valence luminescence via Zn-doping in cesium magnesium chlorides - Daniel Rutstrom; Luis Stand; Maciej Kapusta; Dylan Windsor; Haixuan Xu; Charles L. Melcher; Mariya Zhuravleva (Optical Materials: X)
Scintillators with faster timing capabilities are currently in high demand for use in radiation detection systems in the fields of nuclear and medical physics. The limited number of suitable materials that meet the performance criteria of next generation detection systems presents an opportunity for discovery of new fast scintillator materials. In this work, the effects of doping several ultrafast core-valence luminescent (CVL) scintillators with divalent Zn is explored. Three compounds are investigated – CsMgCl3, Cs2MgCl4, and Cs3MgCl5 – and single crystals of each doped with 5 mol% Zn are grown via the Bridgman method. Additionally, mixing across the full range of concentrations (from 0 % to 100 % Zn) is explored in the Cs2Mg1-xZnxCl4 and Cs3Mg1-xZnxCl5 systems. For low concentrations of Zn, light yields of all three compounds are enhanced (by up to ∼60 %) compared to the pure crystals, achieving what we believe to be the brightest known CVL, CsMgCl3:Zn 5 % (3400 ± 170 ph/MeV light yield). More importantly, Zn doping does not affect the ultrafast timing properties, with each composition maintaining a single-component decay time around 1–3 ns. A sub-100 ps coincidence time resolution (CTR) is also achieved with CsMgCl3:Zn 5 %. The results of this work reveal a new avenue towards obtaining brighter CVL materials, which could open up possibilities for more advanced ultrafast scintillators to be discovered moving forward.